2018
DOI: 10.1536/ihj.17-084
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptors 2 and 4 Predict New-Onset Atrial Fibrillation in Acute Myocardial Infarction Patients

Abstract: SummaryMyocardial infarction (MI) can cause new-onset atrial fibrillation (AF) due to cardiac remodeling. As a recent study has shown, inflammatory factors are closely tied to cell death and survival in myocardial ischemia injury. Toll-like receptors (TLRs) have been shown to participate in the process of myocardial infarction as innate immune factors.The subjects were divided into 3 groups: healthy controls (n = 82), MI patients (n = 84), and AFMI (newonset atrial fibrillation after myocardial infarction) pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 31 publications
(32 reference statements)
0
25
0
Order By: Relevance
“…Among the identified hub genes, CXCR2, TLR4 and CXCR4 were the top 3 genes. Recent studies have demonstrated that CXCR2 has been implicated in the pathogenesis of Ang-II-induced cardiac remodeling [24,25]. Atrial remodeling, such as atrial fibrosis, contributes to the pathogenesis of atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the identified hub genes, CXCR2, TLR4 and CXCR4 were the top 3 genes. Recent studies have demonstrated that CXCR2 has been implicated in the pathogenesis of Ang-II-induced cardiac remodeling [24,25]. Atrial remodeling, such as atrial fibrosis, contributes to the pathogenesis of atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial remodeling, such as atrial fibrosis, contributes to the pathogenesis of atrial fibrillation. TLR4 has been reported to be related to new-onset atrial fibrillation in acute myocardial infarction [25]. Soppert's study has shown that CXCR4 is involved in myofibroblast necroptosis, which may modulate cardiac remodeling in heart failure [26].…”
Section: Discussionmentioning
confidence: 99%
“…Except for sympathetic nerve remodeling, cardiac structure remodeling also plays a critical role in the occur-rence of arrhythmias after MI, 33) especially beyond the subacute period after MI. 4) Myocardial remodeling, characterized by death of normal myocardial cells and formation of fibrosis and scar tissue, is the response to variable environment stimuli including myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…From that perspective, the present findings are promising for discerning the risk of AF in the setting of AMI at an early phase. In this article, the expression of TLR2 and TLR4 in PBMCs of AMI patients had an association with AF onset, 14) but it is uncertain whether PBMCs expressing high levels of TLR2 and TLR4 themselves are initiators of AF, and whether high TLR2 and TLR4 PBMCs are the same population as low TLR2 and TLR4 cells. In any event, further studies will be needed to develop a novel strategy against AF in the setting of AMI, and anti-inflammatory therapy to inhibit AF will be one of the candidates for improving the mortality of AMI and suppressing its burden.…”
Section: Cd16mentioning
confidence: 97%
“…14) They collected blood samples before any reperfusion therapy within two hours after AMI onset, and divided the clinical subjects into two groups: patients with new-onset AF in 1 month after AMI (AFMI group) or without (MI group). The results showed that the expressions of both TLR2 and TLR4 in PBMCs in the MI group were higher than that in healthy volunteers, and much higher in PBMCs in the AFMI group.…”
Section: Article P64mentioning
confidence: 99%